2019
DOI: 10.1007/978-3-030-24409-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transfer Learning for Named Entity Recognition

Abstract: State-of-the-art named entity recognition (NER) systems have been improving continuously using neural architectures over the past several years. However, many tasks including NER require large sets of annotated data to achieve such performance. In particular, we focus on NER from clinical notes, which is one of the most fundamental and critical problems for medical text analysis. Our work centers on effectively adapting these neural architectures towards lowresource settings using parameter transfer methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Similarly, [33] showed that pre-training a BiLSTM-CRF model on a silver standard corpus of 5M sentences from PubMed abstracts, tagged using a trained CRF model rather than human experts, boosts performance on downstream biomedical NER tasks for different entity types. Other work, including [34][35][36][37][38], explore other variations of transfer learning and come to similar conclusions that transfer learning can significantly improve performance on downstream NER tasks. We extend these previous works by (1) comparing the effectiveness of three NER pre-training corpora of differing size and quality and (2) incorporating semi-supervised learning after transfer learning to further improve the performance of our NER approaches.…”
Section: Related Workmentioning
confidence: 77%
“…Similarly, [33] showed that pre-training a BiLSTM-CRF model on a silver standard corpus of 5M sentences from PubMed abstracts, tagged using a trained CRF model rather than human experts, boosts performance on downstream biomedical NER tasks for different entity types. Other work, including [34][35][36][37][38], explore other variations of transfer learning and come to similar conclusions that transfer learning can significantly improve performance on downstream NER tasks. We extend these previous works by (1) comparing the effectiveness of three NER pre-training corpora of differing size and quality and (2) incorporating semi-supervised learning after transfer learning to further improve the performance of our NER approaches.…”
Section: Related Workmentioning
confidence: 77%
“…Note that, when an entity mention is a single word, the function E will behave exactly like the original mapping C. In this paper, we investigate two different approaches for obtaining embedded representations of named entities. The first one, named BERT s , consider a named entity as a document 3 . In the second one, named BERT t , we further investigate the model by extracting the embeddings of single words within the context of the sentence.…”
Section: The Proposed Solutionmentioning
confidence: 99%
“…The Bi-LSTM network is coupled with the use of CRF models for sequence labeling in source and target domains separately to avoid annotation efforts. Additionally, Bhatia et al presented a framework in [3] for performing named entity recognition for domains with low resources such as medicinal texts. They proposed a tunable transfer learning architecture to counter the data scarcity problem, coupled with a parameter sharing approach to transfer overlapped representation from the source to the target domain.…”
Section: Related Workmentioning
confidence: 99%
“…Transfer learning has been implemented in various different machine learning tasks, achieving notable results, for instance, textual summarization [4], named entity recognition [5], question answering [6,7], and text classification [8].…”
Section: Transfer Learning In Nlpmentioning
confidence: 99%